Regulation and Private Sector Investment in Infrastructure : Evidence from Latin America - Pargal, Sheoli (World Bank, Washington, DC, 2014)
The author assesses the importance of the regulatory framework as a determinant of private sector investment in infrastructure. She uses recently compiled data on private and public sector investment in the water, power, telecommunications, railroads, and roads sectors between 1980 and 1998 in nine countries in Latin America. The author finds that the most significant institutional determinant of private investment volumes is the passage of legislation liberalizing the investment regime. This is important because it indicates that the legal basis for reform is probably more critical in determining the quality of the investment climate than specific aspects of the institutional framework governing private sector participation. In accordance with intuition, the author's results indicate that government action to increase regulatory certainty and minimize the perceived risk of expropriation through the establishment of independent regulatory bodies is a critical determinant of the volume of private investment flows. She also finds that the general relationship of private to public investment is one of substitutability.